Mapping the Landscape of Human Resource Management in Education: A Bibliometric Review of Teacher Performance - Aulia Silmi; Hasbiyallah Hasbiyallah; Raudhaturrahima Raudhaturrahima (Universitas Nurul Jadid, 2026)
Human resource management (HRM) is one of the key factors that determine the sustainability and success of the education system. However, in reality, human resource management (HRM) research in education still faces several academic gaps that warrant serious attention. This study aims to analyze the development and scientific underpinnings of Human Resource Management (HRM) in education and identify its implications for improving teacher performance. The approach was a bibliometric analysis of publications indexed in Scopus using VOSviewer. Data were analyzed using word co-occurrence techniques to identify relationship patterns, research clusters, and key trends in the HRM literature. The visualization results show that HRM occupies a central position and is closely connected to performance, leadership, competence, and training, indicating the dominance of the strategic human resource management (SHRM) perspective in the research. In addition, research explicitly linking HR practices to teacher performance at the school level remains relatively rare. These findings confirm the existence of research practice gaps and research opportunities, especially in the context of context-specific HRM in schools in developing countries. This study contributes an integrated map of the field and identifies opportunities for context-sensitive research in underrepresented regions. It also offers direction for designing coherent, ethical, and sustainable teacher-management policies.